Job allocation in the Levy Institute Microsimulation Model - Brandon Istenes (Levy Economics Institute of Bard College, 2025)
The Levy Institute Microsimulation Model (LIMM) is a tool used for policy simulations to estimate ex-ante the employment and income effects of sectoral investments. In Istenes (2023), a simple implementation of the LIMM for New York State initially had difficulty producing realistic conditional distributions of allocated jobs. This paper identifies the sources of that problem, which produces significant distortions to the characteristic distributions of job recipients. Solutions to the problem are presented with theoretical and empirical analysis. The relevance of this problem to other LIMM-based models is discussed; while it is theoretically relevant, it is unlikely to have a substantial impact on results.
Keywords: C53; C63; J16; J21; 330; Employment Simulation; Statistical Matching; LIMM